ANALISIS DAMPAK PERUBAHAN IKLIM TERHADAP KEBERLANJUTAN USAHA (PRODUKSI) GARAM RAKYAT DI PESISIR KABUPATEN JENEPONTO - Rizky Yudha Pahlawan; Asbar Asbar; Ernaningsih Ernaningsih (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2020)
The current global climate change also has an influence on climate or season in Indonesia. Coastal communities in Jeneponto who work as farmers salt still traditional. Dependence of production activities with weather and climate conditions causes the amount of production to fluctuate. This research aims to (1) analyzing climate projections (rainfall and season length), (2) estimating salt production, and (3) knowing the effect of climate change on the business sustainability (production) of salt in the future. Observation rainfall, RCP 4.5 scenario, and salt production data from 2009 to 2018 were regressed and analyzed descriptively and temporally up to 2100. The results showed an increasing in rainfall and dry season are becoming shorter. The estimated percentage of occurrence salt production above average is 51,3%. Climate change gives effect on salt farming time is getting shorter and salt crystallization time is getting longer. Salt production is more affected by rainfall than season length. The business sustainability (production) of salt in the future is still quite good and need for adaptation measures to face climate change.